(untitled) (Research, Society and Development, 2020)
Science education is an essential field for scientific education for people, and this teaching can and should be started from the earliest age, still in early childhood education, seeking to train critical and scientifically literate people. However, for the occurrence of this training in science, it is necessary the action of teachers prepared in order to allow their students different experiences and knowledge specific to the area. Thus, in order to investigate how science teaching in early childhood education is being handled, as well as teacher training for this endeavor, a systematic review was carried out on articles, theses and dissertations on the theme “science teaching in early childhood education”. Kitchenham’s (2004) methodology for systematic literature review was listed as a methodological procedure. The databases listed were journals listed in the Sucupira / CAPES Platform WebQualis, with a survey period from 1996 to 2019 and theses and dissertations listed in the Brazilian Digital Library of Theses and Dissertations, in the period from 2000 to 2019. As a result, it was found that out of a sample of 3,840 works, only 45 dealt with the theme, of which only 12 addressed the training of teachers for science teaching in early childhood education. This result highlights the need for training proposals for teachers, although there has been a growing interest in it in recent years. Thematic categories were established, from the survey, which may serve as a basis for future research.